PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MEDIASI PADA SEKTOR MANUFAKTUR YANG TERDAFTAR PADA IDX TAHUN 2018-2020 - Winny Ratanadewi; Henryanto Wijaya (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to determine the effect of profitability, firm size, and firm growth on firm value with capital structure as a mediating variable in manufacturing companies registered on the Indonesia Stock Exchange in 2018-2020. The analysis technique used path analysis. This study used 72 manufacturing companies as a sample. The results of this study indicated that profitability and firm growth have an insignificant effect on capital structure. However, firm size has a significant effect on capital structure with confidence level of 90% (α=10%). Profitability and firm size have a significant effect on firm value. In contrast, firm growth and capital structure have an insignificant effect on firm value. This study shows that capital structure can't mediate the effect of profitability, firm size, and firm growth on firm value.